2010
DOI: 10.9771/cmbio.v9i3.4527
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da microbiota associada à Pseudolynchia canariensis coletadas em pombos domésticos (Columba livia)

Abstract: ResumoPombos domésticos (Columba livia) são frequentemente encontrados em ambientes urbanos e carreiam grandes quantidades de microrganismos como bactérias (família Enterobacteriaceae) e fungos (Cryptococcus, Histoplasma e Candida), sendo alguns deles causadores de doença em humanos. Entre as penas desses hospedeiros, vive a mosca chamada Pseudolynchia canariensis (Diptera: Hippoboscidae), um inseto hematófago que pode albergar micro-organismos patogênicos ao homem. O objetivo deste estudo foi pesquisar a flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…According to Amaral et al (2012) , in Brazil, there are reports of two species of haematophagous flies present on domestic pigeons: Pseudolynchia canariensis and Pseudolynchia brunei . Marques et al (2010) reported the presence of bacteria and fungi as well as eggs of certain endoparasites in the legs and buccal apparatus of this species of flies, indicating a possible role of these insects in the mechanical deposition of infectious and parasitic agents onto domestic pigeons.…”
Section: Discussionmentioning
confidence: 87%
“…According to Amaral et al (2012) , in Brazil, there are reports of two species of haematophagous flies present on domestic pigeons: Pseudolynchia canariensis and Pseudolynchia brunei . Marques et al (2010) reported the presence of bacteria and fungi as well as eggs of certain endoparasites in the legs and buccal apparatus of this species of flies, indicating a possible role of these insects in the mechanical deposition of infectious and parasitic agents onto domestic pigeons.…”
Section: Discussionmentioning
confidence: 87%